Queer Death Studies: Coming to Terms with Death, Dying and Mourning Differently. An Introduction - Radomska, Marietta; Mehrabi, Tara; Lykke, Nina (Kvinder, Køn & Forskning, 2019)
This special issue aims to rethink death, dying and mourning through theoretical and methodological modes of queering. These modes are mobilised under three overarching themes: (1) queer (necro)politics, which focuses not only on regimes and technologies that subjugate “life to the power of death” (Mbembe 2003, 39), while rendering some lives more grievable than others, but also, on queer modes of resistance; (2) posthuman ethico-politics of death, which seeks to problematise and undermine human exceptionalism, while exploring human/nonhuman relationalities in the context of death and dying; and (3) queering death and mourning, which concentrates on nonnormative practices of remembering and mourning the dead.